The economic agenda of the Polish round table 15 years later: Lessons for the future - Wladyslaw Baka (Transformation, Integration and Globalization Economic Research (TIGER), 2004)
Fifteen years ago, on April 5, 1989, after two months' negotiations between the coalition government and the Solidarity-led opposition, the Round Table agreements set in motion the transformation process. Today, Poland is on the eve of a landmark event - the accession to the European Union, as of May 1. These two occasions are intimately linked. There would be no Polish membership in the European Union without the Round Table talks. In this context, some vital questions need to be addressed. Did Poland take full advantage of the opportunities for socio-political transformation and economic development opened up by the Round Table agreements? What conclusions follow from the experience of the past 15 years for the formulation of a transformation strategy and socio-economic policy that will allow us in the coming years to take advantage of the new opportunities, especially those presented by Poland's membership in the European Union, to the fullest extent possible?
Keywords: 330; Systemtransformation; Systemtransformation; Wirtschaftspolitik; EU-Mitgliedschaft; Polen